PENGARUH LINGKUNGAN KELUARGA DAN MOTIVASI BELAJAR TERHADAP PERILAKU BELAJAR SISWA DI MAN 2 SEMARANG - Soffatunni’mah, Elya; Thomas, Partono (Economic Education Analysis Journal, 2017)
Tujuan penelitian ini adalah untuk mengetahui adanya pengaruh lingkungan keluarga dan motivasi belajar terhadap perilaku belajar siswa kelas XI IPS mata pelajaran ekonomi akuntansi di Madrasah Aliyah Negeri 2 Semarang tahun pelajaran 2016/2017 baik secara simultan maupun parsial. Populasi dalam penelitian ini seluruh siswa kelas XI IPS Madrasah Aliyah Negeri 2 Semarang berjumlah 121 siswa. Pengambilan sampel menggunakan non probability sampling yaitu dengan teknik sampling jenuh, yaitu dengan menggunakan seluruh populasi sebagai sampel. Metode yang digunakan dalam pengambilan data adalah angket atau kuesioner dan wawancara. Data variabel yang diperoleh dianalisis dengan analisis statistik deskriptif dan analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa terdapat pengaruh antara lingkungan keluarga dan motivasi belajar terhadap perilaku belajar siswa kelas XI IPS di MAN 2 Semarang secara simultan sebesar 44%. Pada lingkungan keluarga terhadap perilaku belajar siswa secara parsial berpengaruh sebesar 24,3%. Sedangkan motivasi belajar terhadap perilaku belajar siswa sebesar 11,5%. This research is a quantitative research with a survey method. The population in this study were the students of Social Science Class who were taking Economics and Accounting lesson in second years of Islamic Senior High School as many as 121 students. Samples taken with consecutive sampling technique. This study used a questionnaire and interview as data collection tools. Data were analyzed with descriptive statistical analysis and multiple linear regression analysis. The results showed that family environment and learning motivation toward students’ learning behaviour in this social science class years of 2016 (44%). Partial effect was also obtained in each independent variable on the dependent variable. Effect of family environment to the students’ learning behaviour (24,3%). Furthermore, the learning motivation towards the students’ learning behaviour (11,5%). Based on the results, it can be concluded that family environment and learning motivation influence simultaneously or partially to the students’ learning behaviour in this social science class in their second years at Islamic Senior High School force in 2016. The advice given in order to increase students’ learning behaviour in the way they do group study in order to be independent or not heavily dependent on the other members, education should be more applied at home to solidify what they have learned at school, and parents should pay attention to the development of their childrens’ study and makes collaboration with the school to improve their learning motivation.